Implementation of uMMp using the localization of web objects in user interface design - Aslina Baharum; Azizah Jaafar (UTM Press, 2015)
Websites play an important role as a communication tool between people around the world. This phenomenon introduces the medium of communication, the user interface (UI), between humans and machines as a key player. The existing web development process recognizes this importance but does not follow any precise guidelines for the construction of UI as an activity within the system development life cycle. This paper describes a method for constructing UI based on users’ Mental Model patterns (uMMp) from the localization of web objects. This method can be incorporated into the development process in order to better fulfill users’ expectations. The uMMp describe interface design solutions favouring the development of a UI.